Specific α7 nicotinic acetylcholine receptor agonist ameliorates isoproterenol‐induced cardiac remodelling in mice through TGF‐β1/Smad3 pathway. (18th September 2017) - Yang, Yong‐Hua; Fang, Huan‐Le; Zhao, Ming; Wei, Xiang‐Lan; Zhang, Ning; Wang, Shun; Lu, Yi; Yu, Xiao‐Jiang; Sun, Lei; He, Xi; Li, Dong‐Ling; Liu, Jin‐Jun; et al.
Summary: It is well‐accepted that inflammation plays an important role in the development of cardiac remodelling and that therapeutic approaches targeting inflammation can inhibit cardiac remodelling. Although a large amount of evidence indicates that activation of α7 nicotinic acetylcholine receptor (α7nAChR) causes an anti‐inflammatory effect, the role of α7nAChR in cardiac remodelling and the underlying mechanism have not been established. To investigate the effect of the specific α7nAChR agonist, PNU282987, on cardiac remodelling induced by isoproterenol (ISO 60 mg/kg per day) in mice, the cardiomyocyte cross‐sectional area (CSA) and collagen volume fraction were evaluated by hematoxylin and eosin (HE) and Masson staining, respectively. Cardiac function and ventricular wall thickness were measured by echocardiography. The protein expressions of collagen I, matrix metalloproteinase 9 (MMP‐9), transforming growth factor β1 (TGF‐β1), and Smad3 were analyzed by Western blot. ISO‐induced cardiac hypertrophy, characterized by an increase in the heart weight/body weight ratio, CSA and ventricular wall thickness. Moreover, cardiac fibrosis indices, such as collagen volume fraction, MMP‐9 and collagen I protein expression, were also increased by ISO. PNU282987 not only attenuated cardiac hypertrophy but also decreased the cardiac fibrosis induced by ISO. Furthermore, PNU282987 suppressed TGF‐β1 protein expression and the phosphorylation of Smad3 induced by ISO. In conclusion, PNU282987 ameliorated the cardiac remodelling induced by ISO, which may be related to the TGF‐β1/Smad3 pathway. These data imply that the α7nAChR may represent a novel therapeutic target for cardiac remodelling in many cardiovascular diseases.